POLA KOLOKASI DAN MAKNA VERBA DENOMINAL BERAFIKS {-ISE} DALAM TEKS AKADEMIK BERBAHASA INGGRIS - Cahyaningrum, Rahma (Paramasastra : Jurnal Ilmiah Bahasa Sastra dan Pembelajarannya, 2024)
Verbs are one of the main linguistic elements in sentence structures that explain actions, states, or processes. In academic writing, verbs are important in describing concepts and research processes. This research aims to determine the collocation construction of denominal verbs with the affix {-ise} in English academic texts in terms of grammatical collocation patterns and verb meaning categories. This research uses semantic studies with collocation theory (Benson et al., 2010) and verb meaning category theory (Gottfurcht, 2008; Plag, 2002). This research is qualitative research with data in the form of denominal verb lingual units sourced from the British Academic Written English (BAWE) corpus. The methods of data collection are the observing and selection method by using the AntConc corpus tool. The results show that denominal verbs with the {-ise} affix tend to be accompanied by objects in terms of their collocation patterns so that the verbs can be said dominantly to be transitive. On the other hand, the meaning categories of denominal verbs with the affix {-ise} from the context relationship between verbs and collocates produce five categories, including resultative, ornative, locative, causative, and performative.